2018
DOI: 10.1111/xen.12433
|View full text |Cite
|
Sign up to set email alerts
|

Porcine endothelial grafts could survive for a long term without using systemic immunosuppressors: An investigation of feasibility and efficacy of xeno‐Descemet's stripping automated endothelial keratoplasty from WZS‐pig to rhesus monkey

Abstract: Xeno-DSAEK is feasible and effective, and the technique may reduce the complications common to xeno-PKP. More importantly, the porcine DSAEK grafts could survive for a long term without using systemic immunosuppressors and exhibit promising future for clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Induction therapy and preventions of AMR seem to be crucial, and to date, induction using CS, basiliximab, IVIG, and rituximab and maintenance with tacrolimus and rituximab are a feasible option for human clinical trials based on pig-to-NHP corneal transplantation data ( Choi et al, 2019b ; Kim et al, 2018a ). Since a recent pig-to-NHP endothelial keratoplasty (EK) study showed efficacy under subconjunctival injection of CSs ( Liu et al, 2019 ), this implies that a regional CSs might be an option for patients with compromised endothelial cells.…”
Section: Immunomodulating Agents In Xenotransplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Induction therapy and preventions of AMR seem to be crucial, and to date, induction using CS, basiliximab, IVIG, and rituximab and maintenance with tacrolimus and rituximab are a feasible option for human clinical trials based on pig-to-NHP corneal transplantation data ( Choi et al, 2019b ; Kim et al, 2018a ). Since a recent pig-to-NHP endothelial keratoplasty (EK) study showed efficacy under subconjunctival injection of CSs ( Liu et al, 2019 ), this implies that a regional CSs might be an option for patients with compromised endothelial cells.…”
Section: Immunomodulating Agents In Xenotransplantationmentioning
confidence: 99%
“…Recently, a study on how to produce DMEK graft using porcine cornea has been published ( Liu et al, 2018 ). Regarding Descemet stripping automated endothelial keratoplasty (DSAEK), there was one study reporting long-term survivals of the porcine grafts in NHPs with CS ( Liu et al, 2019 ). However, the graft size was too small (6.0 mm) to apply in human ( Liu et al, 2019 ).…”
Section: Preclinical Efficacy Data Of Porcine Corneal Xenotransplantamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that humoral immunity and cellular immunity are all involved in xeno-corneal transplantation immune rejection. [48][49][50] Choi and colleagues 48 Our previous studies have demonstrated that shortening the processing periods is a useful way to preserve the ultrastructure and characteristics of stromal fibrils during corneal decellularization, and the over-swelling procedure causes a decline or even loss of corneal transparency. 19,20 Regarding the cornea, the sclera is a dense, opaque tissue that is mainly composed of dense interwoven collagen and elastic fibers.…”
Section: F I G U R Ementioning
confidence: 99%
“…For the transplantation to be successful, the thickness of the isolated material has to be reduced by stripping. Liu et al describe the use of Descemet's stripping automated endothelial keratopathy (DSAEK) to process corneas for xenotransplantation . Their work verifies the utility of this method as superior to other methods without the need of immunosuppressive drugs.…”
Section: Corneal Transplantationmentioning
confidence: 99%